2022
DOI: 10.3389/fphar.2022.860682
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Inhibitor Targeting CDT1/Geminin Protein Complex Promotes DNA Damage and Cell Death in Cancer Cells

Abstract: DNA replication initiation requires the loading of MCM2-7 complexes at the origins of replication during G1. Replication licensing renders chromatin competent for DNA replication and its tight regulation is essential to prevent aberrant DNA replication and genomic instability. CDT1 is a critical factor of licensing and its activity is controlled by redundant mechanisms, including Geminin, a protein inhibitor of CDT1. Aberrant CDT1 and Geminin expression have been shown to promote tumorigenesis in vivo and are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Notably, stabilizing CDT1 activity or inactivating Geminin has been shown to induce genotoxic stress in cancer‐derived cell lines, in contrast to non‐transformed cells [28]. Therefore, the development of inhibitors stabilizing CDT1 activity, like the neddylation inhibitor MLN4924 [31], or chemical compounds inhibiting Geminin, or its interaction with CDT1 [32], may lead to specific anti‐cancer agents in CRC. Interestingly, it has recently been reported that mismatch repair‐deficient stage II or III rectal adenocarcinomas are highly sensitive to single‐agent programmed death 1 (PD‐1) blockade [33].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, stabilizing CDT1 activity or inactivating Geminin has been shown to induce genotoxic stress in cancer‐derived cell lines, in contrast to non‐transformed cells [28]. Therefore, the development of inhibitors stabilizing CDT1 activity, like the neddylation inhibitor MLN4924 [31], or chemical compounds inhibiting Geminin, or its interaction with CDT1 [32], may lead to specific anti‐cancer agents in CRC. Interestingly, it has recently been reported that mismatch repair‐deficient stage II or III rectal adenocarcinomas are highly sensitive to single‐agent programmed death 1 (PD‐1) blockade [33].…”
Section: Resultsmentioning
confidence: 99%
“…For CDC6, evidence has been accumulated that it acts as an oncogene promoting tumour progression and as a potential driver of tumourigenesis [ 40 ]. Aberrant CDT1 expression has been reported to promote tumourigenesis, and its small molecular inhibitor showed an obvious tumour-inhibition function by inducing DNA damage [ 41 ]. In addition, we also found that these two genes show a highly positive correlation with multiple tumour-related pathways, such as E2F targets and G2M checkpoint pathways.…”
Section: Discussionmentioning
confidence: 99%